2014
DOI: 10.4269/ajtmh.14-0123
|View full text |Cite
|
Sign up to set email alerts
|

Inadequacy of IgM Antibody Tests for Diagnosis of Rocky Mountain Spotted Fever

Abstract: Abstract. Among 13 suspected Rocky Mountain spotted fever (RMSF) cases identified through an enhanced surveillance program in Tennessee, antibodies to Rickettsia rickettsii were detected in 10 (77%) patients using a standard indirect immunofluorescent antibody (IFA) assay. Immunoglobulin M (IgM) antibodies were observed for 6 of 13 patients (46%) without a corresponding development of IgG, and for 3 of 10 patients (30%) at least 1 year postonset. However, recent infection with a spotted fever group rickettsiae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Some commercial laboratories also perform IFA assays and other serologic testing for IgM antibodies. However, IgM antibodies reactive with R. rickettsii are frequently detected in patients for whom no other supportive evidence of a recent rickettsiosis exists (285). IgM antibodies against ehrlichiae and A. phagocytophilum also might have lower specificity than IgG antibodies (286,287).…”
Section: Serologic Assaysmentioning
confidence: 99%
“…Some commercial laboratories also perform IFA assays and other serologic testing for IgM antibodies. However, IgM antibodies reactive with R. rickettsii are frequently detected in patients for whom no other supportive evidence of a recent rickettsiosis exists (285). IgM antibodies against ehrlichiae and A. phagocytophilum also might have lower specificity than IgG antibodies (286,287).…”
Section: Serologic Assaysmentioning
confidence: 99%
“…Previous studies have shown that after experimental infection, repeat inoculation with Rr elicits no clinical illness, hematological changes, or recall IgM response . Additionally, recrudescent infection with Rr is not thought to occur in dogs or humans . When inoculated with Rr , the 1 dog in this study ( Kat ) that was Rr seroreactive became clinically ill and had a robust IgM response, making it unlikely that she was previously infected with Rr .…”
Section: Discussionmentioning
confidence: 89%
“…While single IgG titers ≥1:64 likely overestimate rickettsial infection, for this study we felt sensitivity was more important in our surveillance case definitions than specificity [32]. We did not assess IgM serological results for laboratory diagnoses, since, unlike for other infectious diseases, IgM is not useful in identifying current or recent rickettsial infections [3,33,34]. We classified cases seropositive for both SFGR and TGR as unspecified Rickettsia infections (URI), since the potential cross-reactivity of the test makes it difficult to determine which group is the cause of the infection.…”
Section: Surveillance Case Classificationmentioning
confidence: 99%